Ms. Bravo and the boss - Rimmer, Christine (Rimmer, Christine. Bravos of Justice Creek., 2016)
Elise Bravo takes the live-in job as an author's assistant to soldier-turned-thriller-writer Jed Walsh, and soon Jed is doing everything possible to make her his, including making friends with her cat, Mr. Wiggles.